Sanctified or Dedicated? hḳdysh in Zephaniah 1:7 - de Jong, John (2018)
Zephaniah 1:7 uses the Hiphil stem of קדשׁ to describe Yahweh sanctifying his guests at a sacrificial meal that he himself has prepared. This is a highly unusual use of קדשׁ Hiphil as it is the Piel and Hitpael stems of קדשׁ that are always used in the ot to describe people entering a holy state in order to participate in cultic activity. The use of the Hiphil signifies that at this sacrificial meal the guests are not sanctified for cultic participation but have rather been dedicated irrevocably to Yahweh, which means they are the sacrifice.
Keywords: Zephaniah 1.7 -- קדשׁ -- Hiphil and Piel -- sacrificial meal -- sanctification and dedication